Efeito do volume de treinamento contrarresistência (musculação) sobre a composição corporal, desempenho físico e parâmetro bioquímico, hormonal e inflamatório em mulheres na pós-menopausa pré-sacrcopênicas - NUNES, Paulo Ricardo Prado (2014)
Sarcopenia and menopause induce negative changes on body composition (BC), physical performance (PP) and biochemical (B), hormonal (H), inflammatory (INF) and metabolic (MET) profile worsening women quality of life. On the other hand, resistance exercise (RE) is a promising intervention which improves these aspects. However, the necessary exercise dosage to improve these aspects has not been completely elucidated. Thus the objective of the study was to evaluate the volume effect of RE on BC, PP, B, H, INF and MET in post menopause women (PM) with pre sarcopenia. 34 PM pre sarcopenic women were randomly allocated into three groups: control (CT = no RE, n=12), low volume (LV = RE with three sets for each exercise, n=10) and high volume (HV = RE with six sets for each exercise, n=12). The LV and HV groups performed total body RE, three times a week, eight exercises at 70 % of 1-RM for 16 weeks. Before and after the training program the BC, PP, B, HP, INF and MET were measured, except by BC and PP which were measured also at eighth week. After eight and 16 weeks of training, the muscle strength gains in HV e BV were greater than CT. After eight weeks of training, only the LV group increased lean body mass (LBM). After 16 weeks, LBM gains were not difference between trained groups. Only the HV group decreased fat body mass (FBM), one mile test time, waist circumference (WC), waist rip ratio (W:C) after 16 weeks. The BV induced a significant decrease above HV in glucose and glycated hemoglobin (HbA1c). Total testosterone (T) and testosterone cortisol ratio (T:C) in HV were reduced when compared to CT and BV respectively. The findings suggest that RE is efficient in increasing strength and LBM independently of volume. HV is more effective in improving FBM, one mile test time, WC and W:C than BV. However, HV induced possible negative effect on glucose, HbA1c, total testosterone and T:C.